Corporate yoga : a primer for sustainable and humanistic leadership - Tripathi, Shiv; Amann, Wolfgang (Emerald Publishing Limited : IAP-Information Age Publishing, Inc., 2017)
Products, services, technologies, and markets are often rather global now - and so are many of our contemporary leadership and sustainability challenges. This book adds to the leadership debate by inspiring leaders, managers, and fellow leadership experts in academia as well as consulting with a new concept. Its authors propose corporate yoga as an effective and innovative idea to fundamentally reframe leadership, anticipate and avoid crises, and handle them differently. Transferring ideas from yogic thinking into the corporate world can generate next-level vision and mission statements. It can alter corporate strategies and governance. Corporate yoga redefines relationships among stakeholder groups, re-energizes organizations, and fosters change towards more sustainable and more humanistic companies and economies.